IDEAS ABOUT THE CORPUS DELICTI AND THE CLASSIFICATION OF CRIMES IN THE CRIMINAL LEGISLATION OF FOREIGN COUNTRIES (World Bulletin of Management and Law, 2022)
This article reveals the issues of legal regulation and ideas regarding the Corpus delicti and the classification of crimes in the criminal legislation of selected developed foreign countries. From a scientific and theoretical point of view, the author analyzes the Corpus delicti, as well as the classification of crimes according to various criteria. In particular, it is noted that at present in foreign countries the corpus delicti is represented by only two elements, and consists of a criminal act (actus reus) and a culpable attitude (mens rea), the subject of the crime does not matter for the doctrine of criminal law. The author analyzes the legal provisions related to the Corpus delicti and the classification of crimes in different countries and formulated scientific and theoretical conclusions
Keywords: Corpus delicti; classification of crimes; act; guilt